Telaah Konsep Landasan Pengembangan Kurikulum - Sabriadi Sabriadi HR; Nurul Wakia (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
The purpose of this study is to have a broad understanding of the foundations of curriculum development as several curriculum foundations have been identified which form the basis for developing the curriculum from various related parties. Curriculum formulation in terms of message, planning, experience is also very important in curriculum development. The curriculum development must refer to or use a strong and solid foundation, so that the curriculum can function and play a role in accordance with educational demands as stated in Law no. 20 of 2003. There are four main foundations that serve as the basis for curriculum development, namely: philosophical foundations, psychological foundations, socio-cultural foundations, and scientific and technological foundations. Philosophical assumptions have implications for formulating educational goals, developing educational content or materials, determining tactics, and the role of students and the role of educators. The psychological basis refers to cognitive, behavioristic and humanistic learning theories. The socio-cultural foundation has implications for the educational programs that will be developed. Meanwhile, scientific and technological foundations are the starting point in disseminating the curriculum so that it is adaptive. Curriculum development is a necessity because changes will definitely occur over time.